Ase1p Organizes Antiparallel Microtubule Arrays during Interphase and Mitosis in Fission Yeast - Isabelle Loïodice; Jayme K. Staub; Thanuja Gangi Setty; Nam-Phuong T. Nguyen; Anne Paoletti; Phong T. Tran (2005)
Proper microtubule organization is essential for cellular processes such as organelle positioning during interphase and spindle formation during mitosis. The fission yeast Schizosaccharomyces pombe presents a good model for understanding microtubule organization. We identify fission yeast ase1p, a member of the conserved ASE1/PRC1/MAP65 family of microtubule bundling proteins, which functions in organizing the spindle midzone during mitosis. Using fluorescence live cell imaging, we show that ase1p localizes to sites of microtubule overlaps associated with microtubule organizing centers at both interphase and mitosis. ase1Delta mutants fail to form overlapping antiparallel microtubule bundles, leading to interphase nuclear positioning defects, and premature mitotic spindle collapse. FRAP analysis revealed that interphase ase1p at overlapping microtubule minus ends is highly dynamic. In contrast, mitotic ase1p at microtubule plus ends at the spindle midzone is more stable. We propose that ase1p functions to organize microtubules into overlapping antiparallel bundles both in interphase and mitosis and that ase1p may be differentially regulated through the cell cycle.